System design for hydrogen gas detection with intelligent embedded communication and Internet of Things integration - Menon, Shyam Kumar; Kumar, Adesh; Mondal, Surajit (Institute of Advanced Engineering and Science, 2026)
The design and analysis of an embedded hydrogen gas detection system embody a complex engineering challenge that integrates sensor technology, embedded system design, and safety engineering. The fast advancement of microcontrollers, energy-efficient electronics, and sophisticated sensing algorithms is facilitating the creation of compact, efficient, and dependable hydrogen detection solutions. The research case article focuses on the hardware system design of Hydrogen gas detection. The hydrogen gas detection system includes an MQ8 sensor for gas sensing, a Raspberry Pi-4 as the main controller, Zigbee for wireless communication, a 16×2 liquid crystal display (LCD) for display, a light emitting diode (LED), and a buzzer for alerts, along with supporting circuitry for signal processing. The gas concentration is monitored and verified through the Thingspeak.com Internet of Things platform, which enables wireless data transmission. The designed system is verified based on environmental factors such as temperature and humidity for comprehensive analysis. The system response was analyzed and tested under different threshold conditions, including 300 ppm and 1000 ppm.